The miRNA mir-582-3p suppresses ovarian cancer progression by targeting AKT/MTOR signaling via lncRNA TUG1. Issue 2 (20th December 2021) - Dai, Tianyu; Liang, Junhui; Liu, Wei; Zou, Yonghui; Niu, Feifei; Li, Mengqing; Zhang, Haomeng; Li, Changzhong; Fan, Mingjun; Cui, Guoying
ABSTRACT: Ovarian cancer (OC) is one of the most common malignancies of the female reproductive system. The miRNA miR-582-3p is associated with a variety of tumors, and the aim of this study was to investigate the role and mechanisms of miR-582-3p specifically in ovarian carcinogenesis and progression. Low expression of miR-582-3p was noted in OC tissue and cell lines, and lower expression of miR-582-3p correlated with lower overall survival in OC patients. Knockdown of miR-582-3p promoted the proliferation and migration of OC cells, while overexpression inhibited them. TUG1, a long non-coding RNA, was found to bind to miR-582-3p, and inhibition of lncRNA TUG1 decreased viability and migration and weakened the effect of miR-582-3p knockdown in OC cells. Implantation of OC cells with reduced miR-582-3p caused increased tumor growth, while lncRNA TUG1 knockdown suppressed tumor growth and relieved the impact of reduced miR-582-3p in vivo . Phosphorylation of AKT and mTOR were significantly enhanced with decreased miR-582-3p expression, but lncRNA TUG1 knockdown attenuated this trend in vitro and in vivo . The novel miR-582-3p represses the malignant properties of OC via the AKT/mTOR signaling pathway by targeting lncRNA TUG1. This axis may represent valuable prognostic biomarkers and therapeutic targets for OC.